First records of Thryaplax Castro, 2007 and Calocarcinus Calman, 1909 (Crustacea: Decapoda: Brachyura) from the Kermadec Islands, New Zealand - Ahyong, Shane T. (Zootaxa, 2009)
Among the Brachyura from the Kermadec Islands in the invertebrate collection of the National Institute of Water and Atmospheric Research, Wellington, New Zealand (NIWA), are two specimens representing two deep-water species previously not known from the region. Both specimens were collected at the same station, together with the paratypes of the parthenopid crab, Garthambrus tani Ahyong, 2008. The new records are reported below to formally document their occurrence at the Kermadec Islands, New Zealand; both also represent the first records of their respective genera from New Zealand waters.  Measurements of specimens, in millimetres, refer to carapace length (cl) and carapace width (cw).